RAGAM ANAK BERKEBUTUHAN KHUSUS (ABK) DAN PROBLEMATIKA ANAK TUNARUNGU SERTA CARA MENGATASINYA DI SEKOLAH ALAM MAHIRA BENGKULU - Dea Fadilla Chairunisa; Indah Cahyani Futri; Sherly Arlena Utami; Vera Wati; Nova Asvio (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
The research objective with this study is to explore the Variety of Children with Special Needs (ABK) and the Problems of Deaf Children and How to Overcome Them in the Alam Mahira School Bengkulu. This study uses descriptive qualitative research where direct research is spaciousness. The informants in this study were 2 teacher and 1 student from the Alam Mahira Bengkulu School. This research addresses children with special needs by showing photos, videos, letter cards, sentence cards, ear anatomy, miniature objects, finger alphabet, ear models, half body torsos, fruit puzzles, animal puzzles, construction puzzles, cylinders, models. geometry, triangular tower, ring tower, rectangular tower, atlas, globe, wall map, custom house miniature. The results of the study show that there are several types of children with special needs (ABK) found in the field, including learning dyslexia (learning difficulties), ADHD (difficulty focusing), Autism (nervous disorder), Speech Delay (speech delay), Down Syndrome (physical and mental retardation). ), Mental Impairment (abnormalities below average – IQ), Deaf (hearing impairment). In this study it was more focused on children with special needs of the deaf. The results of the research show that deaf children need learning media in the form of visual aids to enrich their language vocabulary. The visual aids include miniature animals, miniature humans, relevant pictures, illustrated library books, and children's play equipment.